Fabrication and Properties of Recycled Cellulose Fibre-Reinforced Epoxy Composites - Low, It Meng; Somers, J.; Kho, H; Davies, Ian; Latella, B. (VSP BV, BRILL ACADEMIC PUBLISHERS, 2009)
Epoxy matrix composites reinforced with recycled cellulose fibre (RCF) were fabricated and characterized with respect to their flexural and impact properties. Reinforcement of the epoxy by RCF resulted in a significant increase in the strain at failure, fracture toughness and impact toughness but only a moderate increase in flexural strength and flexural modulus. The effect of accelerated exposure to seawater on the flexural and impact properties was also investigated. The salient toughening mechanisms and crack-tip failure processes were identified and discussed in light of observed microstructures, in particular the orientation of RCF sheets to the applied load.